1986
DOI: 10.1002/j.1460-2075.1986.tb04245.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene conversion-like mechanisms may generate polymorphism in human class I genes.

Abstract: The nucleotide sequences of the human class I major histocompatibility complex genes HLA‐B27k and HLA‐B27w have been determined. They differ by only four nucleotides over a stretch of 14 bp in exon 2, resulting in three amino acid exchanges at positions 77 (Asp to Asn), 80 (Thr to Ile) and 81 (Leu to Ala). The distribution of these nucleotide substitutions suggests a gene conversion‐like event responsible for the generation of these HLA‐B27 subtypes. The mechanisms underlying the generation of new polymorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…USA 87 (1990) translated region (25,26) is truly a locus-specific marker in these sequences. Segmental exchange between HLA loci has been proposed from patterns of sequence shared between alleles at different loci (27)(28)(29). However, clear-cut divergence of sequence between loci in HLA suggests that intralocus exchanges play a more important evolutionary role than interlocus exchanges in generating polymorphism in humans and the higher primates (29,30).…”
Section: L L L L a A A L Ap T Q T R A G S H S L R T Pty T A V Smentioning
confidence: 99%
“…USA 87 (1990) translated region (25,26) is truly a locus-specific marker in these sequences. Segmental exchange between HLA loci has been proposed from patterns of sequence shared between alleles at different loci (27)(28)(29). However, clear-cut divergence of sequence between loci in HLA suggests that intralocus exchanges play a more important evolutionary role than interlocus exchanges in generating polymorphism in humans and the higher primates (29,30).…”
Section: L L L L a A A L Ap T Q T R A G S H S L R T Pty T A V Smentioning
confidence: 99%
“…The HLA-A3/A9 allele might be 20 We noted some nucleotide differences in exon II and IV but none which would result in amino acid differences. We also found sequence differences within intron I and II when compared with previously published sequences for non-diseased HLA-B*2705 alleles.…”
Section: Discussionmentioning
confidence: 72%
“…We also found sequence differences within intron I and II when compared with previously published sequences for non-diseased HLA-B*2705 alleles. 16 20 24 Clearly, further studies are required to resolve the problem of the association of HLA-B27 with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the strength of the association of the HLA-B27 antigen and AS renders the HLA-B27 gene unique among the class I gene family, the HLA-B27 gene was only recently isolated. Several groups have cloned HLA-B27 gene sequences (see Table I) [4][5][6][7] and the amino acid sequences of four HLA-B27 Subtypes have also been obtained by protein sequencing [8][9][10][11]. The gene Organization has been determined by isolating cDNA and genomic cosmid clones [4,5] from gene libraries construeted of DNA prepared from peripheral white blood cells (PBL) and of RNA isolated from a homozygous B-cell line (B LCL) of persons with no history of disease.…”
mentioning
confidence: 99%
“…The gene Organization has been determined by isolating cDNA and genomic cosmid clones [4,5] from gene libraries construeted of DNA prepared from peripheral white blood cells (PBL) and of RNA isolated from a homozygous B-cell line (B LCL) of persons with no history of disease. Seemann et al [6] reported two HLA-B27 subtype sequences cloned from a B-cell line (HLA-B27.1/27.2) which differ only by four nucleotides resulting in three amino acid exchanges. All HLA-B27 sequences are identical in the protein coding regions, the differences found in the LG2-cDNA sequence being due to cDNA cloning artefacts.…”
mentioning
confidence: 99%